Student speaking skill assessment: Techniques and results - Budi Sanjaya; Wahyu Hidayat (International Journal of Evaluation and Research in Education (IJERE), 2022)
This paper describes the learning techniques of Arabic subjects and the results of the evaluation of students' Arabic speaking skills. This study involved 51 Arabic language teachers and 395 State Madrasah Aliyah students in Jambi Province, Indonesia. This study obtained quantitative and qualitative data. The research instrument used a questionnaire, checklist, and oral test. The data were analyzed descriptively (frequency, percentage, mean and standard deviation), and qualitatively. The results showed that the technique of speaking skills from students' perceptions was at a sufficient level. Likewise, the speaking skill assessment technique from the teacher's perception is at a sufficient level. The results of observations on speaking skills assessment techniques showed that teachers use techniques that do not require prior preparation. The students' Arabic speaking skills are at a sufficient level. Further research needs to explore other techniques in Arabic speaking skills.